«Per amor di poesia (o di versi)» Seminario su Giorgio Caproni - Dolfi, Anna (Moderna/Comparata, 2018)
Giorgio Caproni is certainly among the most loved Italian poets of the 20th century. Anna Dolfi used this widespread passion to involve not only well-known scholars of Caproni, but also young researchers, in new research activities. This results in a considerably rich book which, together with an overall vision, offers a series of hermeneutical insights on themes which were not as frequently investigated until then (memory, bestiaries and so on), by combining new readings of exemplary texts with unpublished documents, with reflections on language and poetry, on musical, pictorial and mythical suggestions, never forgetting Caproni's activity for translation, self-commentary and civic commitment. The book is functionally divided into Percorsi e attraversamenti, Letture (e immediati dintorni), Risultanze tra/dalle carte d'archivio, which enhances the diversity of the critical commentaries and the close comparisons, of the surveys and experiments of comment, of explication de texte, and highlights the great technical skill and the extreme lyrical depth of an author who, between cantability and dissonances, arpeggios and apostrophes, cabalettas and cadences, flourishes and delays, vocalizations and little verses, recoveries and leave, talkativeness and aphasia, was able to interpret the contradictory research, the questions, the fears, the faults and the incurable wounds of our time.